(3GdcGed aj eYQaI VYaGA GdeMOKjf hYdd GdCMGOjKs - (3GHf YOj , YHO Gddg Hf YOj Hf YHO Gddg Hf eMeO Hf GdeHGQc GdLQLGfj, CHh CMeO,J (B365 (3g` s
(3ChdgG (B:s
(3jHOC Hef CSeg (B: (3YHO GdQMef Hf jMji , ef MQa GdYjf s
(3BNQgG (B:s
(3hjfJgi Edi GSe (B: (3eMeO Hf GdMLGL GddNei , ef MQa Gdeje s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B82s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B119 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJGQjNs